MOTIVATION OF NEW STUDENTS OF CONTINUING EDUCATION TO STAI ALHIKMAH JAKARTA - Taufik Abdillah Syukur (STKIP PGRI Situbondo, 2023)
This study aims to determine the motivation of students in continuing their education at STAI ALHIKMAH Jakarta. The type of research used is field research using qualitative methods. The results showed that the majority of new students from the 2021/2022 class had intrinsic motivation in continuing their education at STAI ALHIKMAH Jakarta.